Equity research apple inc - Varão, Vasco Maria Gois Ferreira Proença (2022)
In this part, I continue to analyze the estimated revenues of Apple. I start by analyzing the we are think it will be one of the main drivers of Apple revenues in the following years. Next, I analyze the services and their role in Apple’s long-term survival. As discussed below, I think that it will not be only a source of a great income by it self but will also be the reason for products to continue to sell so well. After, I briefly discuss some additional factors that in the future may became a portion of the revenues. Following that I explain how the valuation of Apple ismadein this report(using a discounted cash flow)and point two crucial factors of the valuation: the weighted average cost of capital and the long term growth rate. To finalize I make a quick analysis using the Porter 5 Forces structure and conclude about the valuation in general.